Sulfonated poly(ether ether ketone)/s–TiO2 composite membrane for a vanadium redox flow battery. Issue 26 (20th December 2019) - Wang, Gang; Wang, Fei; Li, Anfeng; Zhang, Miaomiao; Zhang, Jie; Chen, Jinwei; Wang, Ruilin
ABSTRACT: The SPEEK/s‐TiO2 composite membrane was prepared by blending sulfonated poly(ether ether ketone) (SPEEK) and sulfonated titanium dioxide (s‐TiO2 ) nanoparticles. The important physiochemical parameters such as proton conductivity, water uptake, swelling degree and ion exchange capacity of the composite membrane were measured. The thermal stability and chemical stability were also tested. It was observed that the SPEEK/s‐TiO2 composite membrane exhibited the best selectivity (7.13 × 10 4 S·min·cm −3 ) accompanying high proton conductivity (0.061 S·cm −1 ) and low tetravalent vanadium ion (VO 2+ ) permeability (8.55 × 10 −7 cm 2 ·min −1 ) compared with Nafion117, SPEEK and SPEEK/TiO2 membranes. The battery performance with these membranes was characterized by charge–discharge cycling tests and it was found that the SPEEK/s‐TiO2 composite membrane showed the highest energy efficiency (EE) up to 82.3%, indicating the SPEEK/s‐TiO2 composite membrane is a candidate for vanadium redox flow battery (VRFB) application. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48830. Abstract :